The Effect of Environmental, Social, Governance and Financial Factors on Firm Value in Transportation Companies - Destriani Wibowo; Asep Risman (Dinasti International Journal of Digital Business Management, 2026)
This study examines the effect of Environmental, Social, and Governance practices, capital structure, and profitability on firm value in transportation and logistics companies listed on the Indonesia Stock Exchange during 2020–2024, with firm growth and investment decisions as moderating variables. The research aims to clarify whether sustainability initiatives independently enhance firm value or depend on financial discipline and investment governance. Using a quantitative approach with panel data regression analysis and moderated regression analysis, firm value is measured by Tobin’s Q, capital structure by debt-to-equity ratio, profitability by return on assets, firm growth by sales growth, and investment decisions by investment opportunity set. The findings indicate that Environmental, Social, and Governance practices negatively and significantly affect firm value, capital structure has no significant effect, and profitability positively influences firm value. Firm growth does not moderate these relationships, while investment decisions significantly moderate the effects of sustainability practices and profitability. The results suggest that sustainability initiatives enhance firm value only when aligned with disciplined investment strategies and strong financial performance in a volatile industry environment.